Growth Performance and Biomass Production of Some Agroforestry Tree Species in Nursery in Northeastern Himalayan Region - Tomar, J.M.S.; Bhatt, B.P. (Indian Journal of Agroforestry, 2020)
Growth performance and biomass yield of some important agroforestry tree species was observed under nursery conditions after two years of growth. Among the various species, Alnus nepalensis D. Don., exhibited highest germination percentage followed by Parkia roxburghii G. Don., Pinus kesiya Royle ex Gordon and Gmelina arborea Linn. This study revealed that A. nepalensis (44%) had lowest germination and survival (45.5%) in the nursery condition as compared to other tree species. However, it exhibited highest height, followed by Melia azadirachta Linn. Various parameters of growth, germination and seedling survival varied significantly (P=O.05) among species. Bole height was maximum in M. azadirachta and P. roxburghii while rest of the species exhibited maximum growth in crown height. Although G. arborea showed comparatively low growth in height, it had maximum collar diameter growth and total biomass yield (g plant-1), followed by A. nepalensis. Inter-comparing the component wise dry matter partitioning of various species, root, stem and branch of G. arborea contributed maximum biomass as compared to other species. However, leaf component, was recorded highest in A. nepalensis. Significant (P=O.05) differences were recorded in total biomass production among species, except that of M. azadirachta and P. roxburghii.